PENERAPAN SISTEM MERIT DALAM BIROKRASI INDONESIA UNTUK MEWUJUDKAN GOOD GOVERNANCE - Nur Khobiburrohma, Eviva; Septiana Margareta, Priska; Habbie Hasbullah, MS. (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
In the current era, countries are required to contribute in order to compete with developing and developed countries. The government provides the legal basis governing the State Civil Apparatus, namely Law No. 5 of 2014. The regulation discusses its relation to the merit system based on qualifications, competencies, and performance. With this regulation, planning in developing human resources is needed in order to improve the quality of personnel themselves. The development of good apparatus resources will benefit an organization. One way can be done by providing education and training for apparatuses to improve their competence and quality. The discussion contained in the regulation of Law No. 5 of 2014 explains the management of human resources in accordance with the regulations.